1982
DOI: 10.1113/jphysiol.1982.sp014372
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐activated and calcium‐activated currents studied in solitary rod inner segments from the salamander retina

Abstract: .SUMMARY 1. Solitary rod inner segments were obtained by enzymatic dissociation of the tiger salamander (Ambystoma tigrinum) retina. Their membrane currents were studied with the single-pipette voltage-clamp technique. Individual currents were isolated with the aid of pharmacological agents.2. Extracellular caesium blocked a current activated by hyperpolarization from -30 mV. Changing external sodium and potassium concentrations altered the value of the reversal potential in a manner consistent with the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
301
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(335 citation statements)
references
References 50 publications
31
301
3
Order By: Relevance
“…Moreover, single-channel recordings (Rodriguez-Contreras and Yamoah, 2003) of L-type Ca 2+ channels in hair cells reveal clearly that at any test voltage Ba 2+ results in much greater activation of the channel than Ca 2+ does, i.e., the channel has a much higher open probability in Ba 2+ . Barium also fails to activate significantly calcium-dependent channels, including a Ca 2+ -dependent potassium current (Bader et al, 1982;Moriondo et al, 2001) and a Ca 2+ -dependent chloride current (ICl Ca Maricq and Korenbrot, 1988;. Thus, the use of Ba is beneficial because it allows better isolation of I Ca , but it also obscures functionally important interactions between calcium and calcium-dependent channels (see Section 5.1).…”
Section: Impact Of Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, single-channel recordings (Rodriguez-Contreras and Yamoah, 2003) of L-type Ca 2+ channels in hair cells reveal clearly that at any test voltage Ba 2+ results in much greater activation of the channel than Ca 2+ does, i.e., the channel has a much higher open probability in Ba 2+ . Barium also fails to activate significantly calcium-dependent channels, including a Ca 2+ -dependent potassium current (Bader et al, 1982;Moriondo et al, 2001) and a Ca 2+ -dependent chloride current (ICl Ca Maricq and Korenbrot, 1988;. Thus, the use of Ba is beneficial because it allows better isolation of I Ca , but it also obscures functionally important interactions between calcium and calcium-dependent channels (see Section 5.1).…”
Section: Impact Of Experimental Conditionsmentioning
confidence: 99%
“…Cl − flux can also alter membrane potential and a balance between these two effects may help to stabilize the tonic activation level of I Ca (Thoreson et al, 2003a). To better understand these simultaneous feedback interactions, we consider the case of rods where E Cl is positive to the dark membrane potential (Bader et al, 1982;Somlyo and Walz, 1985;Burkhardt et al, 1991;Thoreson et al, , 2003a. In this scenario, activation of I Ca stimulates I Cl(Ca) , producing a depolarization that leads to further activation of I Ca .…”
Section: Ionic Modulation Of Calcium Channels: Chloride-reducing the mentioning
confidence: 99%
“…In the nervous system functional CaCCs are best characterized in neurons with various sensory functions, such as olfactory neurons (Kleene & Gesteland, 1991; Lowe & Gold, 1993), photosensitive rods and cones (Bader et al . 1982; Maricq & Korenbrot, 1988; Barnes & Hille, 1989), taste cells (Taylor & Roper, 1994) and somatosensory neurons (Liu et al . 2010; Cho et al .…”
Section: Introductionmentioning
confidence: 99%
“…Large hyperpolarizations elicited by bright light activate a Cs + -sensitive inward current (Fain et al, 1978). This inward current, now called I h (Bader et al, 1982), produces, within a few hundred milliseconds, a reduction in the hyperpolarization, by up to 20 mV, that makes the photovoltage peak well in advance of the photocurrent (Bader et al, 1979;Baylor et al, 1984). However, a dim light response of only a few millivolts also peaks sooner than the corresponding photocurrent (Baylor et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Attwell and Wilson (1980) have suggested that one of two current components contributing to the net current elicited by hyperpolarization was a deactivating outward current, I x , which could be recorded in the presence of Cs + and reversed in the region of the K + equilibrium potential. Bader et al (1982) have described a voltage-gated K + current (I K ) and a Ca 2+ -activated K + current, but the role of these currents in the response to dim light has not been addressed. Using whole-cell, patch-clamp techniques applied to isolated rod photoreceptors for high-resolution recording, we characterize the activity of a population of K + channels that gate in the voltage range from -30 to -70 mV.…”
Section: Introductionmentioning
confidence: 99%